Human annexin A5 promotes glioma progression by targeting the MAPK/CD44 pathway - Liu, WeiXian; Xiong, Tao; Sun, Hu; Wang, Ming; Zhu, JunGao; Li, ChuanChuan (Frontiers in Oncology, 2025)
BackgroundGliomas are the most common intracranial malignant tumors. In this study, we aimed to identify the hub genes and investigate the pathophysiological significance of ANXA5 in glioma.MethodsThe differentially expressed genes (DEGs) between tumor and adjacent tissues from glioma patients were acquired from the Gene Expression Omnibus (GEO) database. Functional enrichment analysis and protein-protein interaction (PPI) network construction of overlapping DEGs were performed. The GEPIA and CGGA databases were used to explore hub gene expression. The effect of hub genes on prognosis and tumor-infiltrating immune cells was analyzed via GEPIA, CGGA, and TIMER2 databases. Additionally, ANXA5 expression was measured by qRT-PCR and Western blotting. The effects of ANXA5 were assessed by CCK-8, colony formation, Transwell, and flow cytometry assays. Moreover, the roles of ANXA5 were identified in vivo.ResultsThe DEGs were enriched in cell surface receptor signaling pathway, immune response, and MAPK signaling pathway. The selected hub genes were included ANXA5, STAT1, CD44, CAV1, ANXA2, and MAPT. Among them, expression of ANXA5, STAT1, CD44, CAV1, and ANXA2 was strongly correlated with patient prognosis and was also involved in the tumor microenvironment. Furthermore, ANXA5 knockdown significantly inhibited the migration and proliferation of glioma cells in vitro and in vivo. Meanwhile, we found that the expression of CD44 was monitored by ANXA5, and ANXA5 promoted the migration and proliferation of glioma cells via the MAPK/CD44 pathway.ConclusionTaken together, our data showed that ANXA5 could contribute to cell proliferation and metastasis of glioma by targeting the MAPK/CD44 axis.